Law, Ethics, and Hadith Ahkam: An Analysis of Fatwa MUI in the Perspective of Progressive Interpretation - Anam, Wahidul; Sulaeman, Mubaidi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article discusses the progressive interpretation of the ahkam hadith in MUI Fatwa Number 83 of 2023 which relates to the law of support for the Palestinian struggle, with an emphasis on its relation to the boycott of products that support Israel. The main focus of this research is an in-depth and critical exploration of the relevance of certain hadiths in the context of the Palestinian struggle, as well as their application to the boycott policy as a form of solidarity action. This article adopts the perspective of Abdullah Saeed's progressive interpretation of listening to the hadiths that were used as the basis for the MUI fatwa. The method used in this article is a qualitative method with a hadith ahkam and an ethical-legal approach. The data collection technique is a literature study in the form of a study of hadith, journal articles, books related to law, ethics, and hadith ahkam regarding fatwas. The results of this study provide deep insights into the relevance of ahkam traditions in supporting the Palestinian cause in the context of boycotts. Progressive thinking on these traditions is integrated with arguments to strengthen boycotts in response to human rights violations and economic policies that support Israeli occupation. The article also discusses the potential impact of the boycott, both from an economic point of view and as a political instrument that can exert international pressure. Thus, this article not only attempts to detail the progressive interpretation of hadith ahkam in MUI Fatwa No. 83 of 2023 but also critically relates it to the boycott strategy, contributing to progressive Islamic literature and Islamic law studies in viewing the Israeli-Palestinian conflict.